2017
DOI: 10.21873/anticanres.12112
|View full text |Cite
|
Sign up to set email alerts
|

The “Yin and Yang” of Platelet-rich Plasma in Breast Reconstruction After Mastectomy or Lumpectomy for Breast Cancer

Abstract: Surgery remains the mainstay of treatment for breast cancer, including complete or partial mastectomy and lumpectomy. Breast reconstruction has gained popularity mainly due to its tremendous impact on the psychological status of the patients. Autologous fat grafting is a well-established method used in cosmetic surgery; however, fat re-absoprtion, fat necrosis, calcifications and oil-cyst formation are some usually encountered complications limiting the efficacy of this approach. Platelet-rich plasma (PRP) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
4
0
4
Order By: Relevance
“…We think that this positive effect is due to both the anti-inflammatory properties of PRP and its enhancing properties in local growth factors. However, it is predicted that the application of PRP to the surgical area after cancer operations may have negative effects in terms of tumor treatment (29). Because of this negativity, in our study, the effect of HAM, a biological material reported to have a non-tumorigenic effect, which can be an alternative to PRP, on seroma was investigated (30).…”
Section: Discussionmentioning
confidence: 98%
“…We think that this positive effect is due to both the anti-inflammatory properties of PRP and its enhancing properties in local growth factors. However, it is predicted that the application of PRP to the surgical area after cancer operations may have negative effects in terms of tumor treatment (29). Because of this negativity, in our study, the effect of HAM, a biological material reported to have a non-tumorigenic effect, which can be an alternative to PRP, on seroma was investigated (30).…”
Section: Discussionmentioning
confidence: 98%
“…PRP has a high concentration of growth factors, which encourages the differentiation of stem cells, the proliferation of undifferentiated stem cells and capillaries, as well as the stimulation of endothelial cells and angiogenesis [182][183][184]. PRP is being investigated for usage in mastectomy-related breast reconstruction surgery [185]. In a study on 50 patients with breast soft-tissue abnormalities, Pietro Gentile et al used autologous fat graft with PRP to increase the fat volume in breast reconstruction.…”
Section: Cancermentioning
confidence: 99%
“…При анализе динамики изменения эректильной функции по данным МИЭФ-5 отмечено улучшение с 9,86 ± 6,02 (0-20) до 17,93 ± 4,5 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) балла (р <0,05). На 60-й день исследования также отмечено улучшение по данным ППО: с 1,93 ± 1,49 (0-5) до 3,29 ± 1,69 (2-5) балла (р = 0,002).…”
Section: таблица 2 базовые характеристики пациентовunclassified